ASSESSMENT IN EDUCATION: CONCEPT, TYPES, AND ITS ROLE IN LEARNING OUTCOMES (E Global Congress, 2025)
Assessment plays a crucial role in contemporary education, serving not only as a measurement tool but also as a mechanism to enhance teaching effectiveness and student learning outcomes. This article examines theoretical foundations of assessment, major forms and their pedagogical functions, current research-based practices, and the challenges educators face when implementing assessment systems. The paper further discusses implications for improving educational quality.